Female masculinity - Halberstam, Judith (Zubaan, 2012)
Masculinity without men. In Female Masculinity Judith Halberstam takes aim at the protected status of male masculinity and shows that female masculinity has offered a distinct alternative to it for well over two hundred years. In this first full-length study on the subject, Halberstam catalogues the diversity of gender expressions among masculine women from nineteenth-century pre-Iesbian practices to contemporary drag king performances. Through detailed textual readings as well as empirical research, Halberstam uncovers a hidden history of female masculinities while arguing for a more nuanced understanding of gender categories that would incorporate rather than pathologize them. She rereads Anne Lister's diaries and Radclyffe Hall's The Well of Loneliness as foundational assertions of female masculine identity. She considers the enigma of the stone butch and the politics surrounding butch/femme roles within lesbian communities. She also explores issues of transsexuality among "transgender dykes"-Iesbians who pass as men-and female-to-male transsexuals who may find the label of "lesbian" a temporary refuge. Halberstam also tackles such topics as women and boxing, butches in Hollywood and independent cinema, and the phenomenon of male impersonators. Female Masculinity signals a new understanding of masculine behaviors and identities, and a new direction in interdisciplinary queer scholarship. Illustrated with nearly forty photographs, including portraits, film stills, and drag king performance shots, this book provides an extensive record of the wide range of female masculinities.